CLINICAL AND DIAGNOSTIC ASPECTS OF MANAGING PATIENTS WITH VALVULAR HEART DISEASE - Shaposhnyk, O.A.; Prykhodko, N.P.; Savchenko, L.V.; Shevchenko, T.I.; Sorokina, S.I.; Yakymyshyna, L.I.; Kudria, I.P. (World of Medicine and Biology, 2022)
The article presents the results of examination of 47 patients with valvular heart disease. According to the research findings, when investigating the causes of severe mitral regurgitation, especially in young and middle-aged people, one should primarily consider Barlow’s disease, myxomatous mitral valve degeneration, as the primary cause (having excluded fibroelastic deficiency). It was found that among all cases of detected mitral valve prolapse (even minor or moderate), which is currently diagnosed quite often with the development of modern technology, stratification of patients requires additional examinations to identify people at high risk of disease progression and complications, as well as to determine the prognosis.